Methodology for individualizing the technical and tactical training of qualified karatekas, taking into account the styles of fighting - Burtseva, E.V.; Igoshina, N.V.; Igoshin, V.Y. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to theoretically substantiate the content and direction of the methodology for individualizing the technical and tactical training of qualified karatekas, taking into account the styles of fighting. Methods and structure of the study. To achieve this goal, the following research methods were used: theoretical analysis and generalization of scientific and methodological literature; pedagogical observation; video analysis of competitive activities; pedagogical experiment; mathematical and statistical methods. The study was conducted on the basis of the «Sports School» of the Alkeevsky district of the Republic of Tatarstan. The experiment involved 11 athletes involved in Kyokushin (Master of Sport qualifications – 2 people, Candidate of the Master of Sports - 9 people) (weight category 65-75 kg). Results and conclusions. The content and direction of the methodology for individualizing the technical and tactical training of qualified karatekas, taking into account the styles of fighting, have been developed. The content of the technical and tactical training methodology includes two sections: (1) Improvement of the individual style of conducting a competitive duel; (2) elimination of gaps in technical and tactical actions in duels. The content and direction of the technical and tactical training methodology was carried out individually for each karateka, taking into account the arsenal of technical and tactical actions, preferred tactics of fighting, the content and structure of competitive activity, the number of signature techniques brought to perfection, the level of motivation to achieve the highest results, the ability to rebuild tactics fighting depending on the current situation.